Akad Tabarru’ Pada Pengolahan Limbah Industri di Desa Wantilan Kecamatan Cipeundeuy Subang - Siti Rohmat; Widaningsih; Rina Nurhayati (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2021)
In order to reduce waste and optimize existing potential, the Wantilan Village Government manages waste from industry in the form of rope waste into creative handicraft products and has economic value. Through the Family Welfare Trustees (PKK) in Wantilan Village, the waste rope that was previously trash has now been transformed into a bag, a place for tissue, flower pots and others. The community as craftsmen certainly has additional income from these handicraft products so that this program can certainly increase the income of the community, especially the craftswomen. The purpose of this study was to find out the practice of tabarru' contracts in industrial waste treatment in Wantilan Village, Cipeundeuy District, Subang Regency, to find out industrial waste treatment carried out in Wantilan Village, Cipeundeuy District in the view of Islamic Economics, and to find out the benefits of tabarru' contracts for anayaman craftsmen. Wantilan Village, Cieundeuy District, Subang Regency. The type of research used is field research, while the approach used in this research is a descriptive-qualitative approach. The practice of processing industrial waste in Wantilan village is a tabarru contract with a monetary contribution of IDR 10,000 per sack. In industrial waste treatment in Wantilan Village, there are two tabarru' contracts in the form of giving something, namely a grant contract that is in accordance with sharia provisions. The benefits of the Tabarru' contract that have been carried out include the profit from the sale of handicrafts is quite large because craftsmen do not need to buy raw materials, craftsmen can easily get raw materials because they have been provided by the manager, tools or general expenses needed by the PKK for mutual progress in pay from tabarru' funds, as for these needs including: making hangtags, exhibition needs, purchasing raw materials to the company.